Interphase Nuclear Structure in Ten Species of Pteridophytes (Journal of Bio-Science, 2021)
In thelypterids, interphase chromosomes of Ampelopteris prolifera were accompanied by two or three nucleoli. One nucleolus was seen floating outside the nucleus while other remained attached with the nucleus in annular cells of Christella arida. The mean of chromocentres determined in Adiantum species ranged from 49.8 to 53.6, whereas, it ranged from 46.6 to 49.5 in Pteris species. On the other hand, the value for chromocentres ranged from 62.5 to 123.5 in thelypterids. Nuclear organization was observed to be chromocentric type. In case of interphase nuclear volume it was observed that in Adiantum it was highest in A. capillus-veneris followed by A. caudatum and A. lunulatum, in Pteris it was highest in P. biaurita followed by P. vittata and P. griffithi, and in case of thelypterids, it was highest in C. dantata followed by C. Cylindrothix, A. Prolifera and C. arida.J. Bio-Sci. 29(2): 93-98, 2021 (December)